Nordic late blight observations - Lehsten, Veiko (Lund University, 2017)
Observed late blight incidence and simulated weather data used in the study “Earlier occurrence and increased explanatory power of climate for the first incidence of potato late blight caused by Phytophthora infestans in Fennoscandia". Data is collected on two sites in Finland, Lammi (61°05’ N; 25°01’ E) and Jokioinen (60°49’ N; 23°30’ E), from 1988 to 2011, and at three sites in Sweden, Mosslunda (55°58’ N, 14°6.3’ E) Borgeby (55°45’ N, 13°2.3’ E) and Lilla Böslid (56°36’ N, 12°57’ E), from 1983 to 2012.
Keywords: Environmental Sciences; Miljövetenskap